2009
DOI: 10.1021/mp900018v
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticle Drug Carriers and Their Study by Quadrupole Magnetic Field-Flow Fractionation

Abstract: Magnetic nanoparticle drug carriers continue to attract considerable interest for drug targeting in the treatment of cancers and other pathological conditions. The efficient delivery of therapeutic levels of drug to a target site while limiting nonspecific, systemic toxicity requires optimization of the drug delivery materials, the applied magnetic field, and the treatment protocol. The history and current state of magnetic drug targeting is reviewed. While initial studies involved micron-sized and larger carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 191 publications
1
37
0
Order By: Relevance
“…For the purpose of efficiently exploiting the EPR effect for disease detection as well as cancer treatment, the molecular weight of a drug should be more than 40 kDa (Maeda et al, 2009). Cut-off sizes for pores in cases of various tumors are in the range between 380 and 780 nm (Brigger et al, 2002;Williams et al, 2009). …”
Section: Cancer Pathologymentioning
confidence: 99%
“…For the purpose of efficiently exploiting the EPR effect for disease detection as well as cancer treatment, the molecular weight of a drug should be more than 40 kDa (Maeda et al, 2009). Cut-off sizes for pores in cases of various tumors are in the range between 380 and 780 nm (Brigger et al, 2002;Williams et al, 2009). …”
Section: Cancer Pathologymentioning
confidence: 99%
“…23 Magnetic nanoparticles have been used in drug delivery and rapid biological separation. [24][25][26][27][28][29][30][31][32] Several previous studies demonstrated that DNA molecules can bind to magnetic nanoparticles by noncovalent bonds and have used this capacity to increase transfection efficiency by applying a magnetic field to the target site. [33][34][35][36][37][38] To further develop this novel treatment for ACC, we used polymer-modified iron oxide nanoparticles as vector, prepared by alkaline co-precipitation in the presence of the cationic polymer PEI.…”
mentioning
confidence: 99%
“…The quadrupole magnetic field-flow fractionation (QMgFFF) system has been described previously (Carpino et al 2005a(Carpino et al ,b, 2007Williams et al 2009a). The quadrupole electromagnet was designed and assembled in our laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Early attempts to develop MgFFF were not generally very successful for various reasons principally associated with non-ideal channel geometry and field arrangements. The literature concerning these early attempts has been described by us previously (Carpino et al 2005a,b;Williams et al 2009a). It was noted above that FFF optimally requires the field and/or field gradient to be uniform across the breadth of the channel, and that the channel also be of uniform thickness across its breadth.…”
Section: Introductionmentioning
confidence: 99%